Emerging Therapeutic Approaches for Cystic Fibrosis. From Gene Editing to Personalized Medicine - Pranke, Iwona; Golec, Anita; Hinzpeter, Alexandre; Edelman, Aleksander; Sermet-Gaudelus, Isabelle (Frontiers in Pharmacology, 2019)
As our knowledge of the Cystic Fibrosis (CF) Transmembrane conductance Regulator (CFTR) structure and consequences of mutations has improved, the new therapies target specific defects in the CFTR gene to restore CFTR expression and function. Some strategies are mutation-specific and have already reached clinical development. This includes read-through of specific premature termination codons (read-through therapies, Non Sense Mediated Decay pathway inhibitors for Class I mutations); correction of CFTR folding and trafficking to the apical Plasma Membrane (correctors for Class II mutations); increase in the CFTR channel function (potentiators therapy for Class III mutations and any mutant with residual function located at the membrane). Others are not mutation-specific and are still in preclinical development. Their aim is the genome editing (gene therapy) or repairing the airway tissue (stem cell therapy). Such strategies directed to the basic defects are now revolutionizing treatment for patients with CF and should positively impact on their survival.